2003
DOI: 10.1210/en.2003-0537
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of Testosterone, 17β-Estradiol, and Progesterone on Adrenergic Regulation in Cultured Brown Adipocytes: Potential Mechanism for Gender-Dependent Thermogenesis

Abstract: Previous studies suggest that sex hormones could be responsible, at least in part, for the gender-dependent thermogenesis found in the adrenergic control of brown adipose tissue (BAT) under control conditions and in response to diet and cold. Catecholamines, as well as several hormones, including sex hormones, may alter the function or expression of different adrenoceptor subtypes in brown adipocytes in vivo, and a confirmation could be provided by in vitro experiments. Therefore, the effect of testosterone, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 43 publications
4
78
1
3
Order By: Relevance
“…Indeed, progesterone stimulates Ucp1 mRNA expression and NE-mediated lipolysis (Monjo et al 2003) in cultured brown adipocytes. Further indirect findings highlight the role of progesterone as an enhancer of BAT activity.…”
Section: Progesterone and Bat Thermogenesismentioning
confidence: 98%
“…Indeed, progesterone stimulates Ucp1 mRNA expression and NE-mediated lipolysis (Monjo et al 2003) in cultured brown adipocytes. Further indirect findings highlight the role of progesterone as an enhancer of BAT activity.…”
Section: Progesterone and Bat Thermogenesismentioning
confidence: 98%
“…In this respect, we have previously investigated in rats the overall effect of sex and regional locations of the adipose tissue on some of the mechanisms affecting the lipolytic capacity, such as adrenergic receptor balance (45, 48) and several cascade steps at the postreceptor level, such as adenylyl cyclase, protein kinase A and hormone-sensitive lipase (45). It has been suggested that these sex-dependent differences are due to variations in the hormonal environment, as sex hormones play an important role in the adipose tissue metabolism (32,48).Previous studies in rodents and humans have demonstrated that sex hormones are involved in the direct modulation of adipose tissue metabolism at multiple levels, acting at different steps of the lipolytic and lipogenic pathways (18, 23); coactivating or modulating the expression of adipogenic transcription factors (23); and altering the adipocyte proliferation (1), the glucose metabolism (15), and the expression of several adipocyte hormones (26,35,50,56).In addition to serving as a steroidal reservoir, adipose tissue is one of the most important extragonadal sources of steroids, due to the specific expression of steroidogenic enzymes, such as aromatase (4), suggesting a potential impact on the local adipose tissue metabolism that would be independent of the sex hormone plasma milieu (53). Steroid hormones exert their effects through specific receptors that belong to the superfamily of nuclear hormone receptors, which are widely expressed in several tissues including adipose tissue (7,10,20,21,31,36).…”
mentioning
confidence: 99%
“…In this respect, we have previously investigated in rats the overall effect of sex and regional locations of the adipose tissue on some of the mechanisms affecting the lipolytic capacity, such as adrenergic receptor balance (45, 48) and several cascade steps at the postreceptor level, such as adenylyl cyclase, protein kinase A and hormone-sensitive lipase (45). It has been suggested that these sex-dependent differences are due to variations in the hormonal environment, as sex hormones play an important role in the adipose tissue metabolism (32,48).…”
mentioning
confidence: 99%
“…Although currently undetermined, this process may involve altered expression of adrenoreceptors. 4 Of relevance are the reported effects of levonorgestrel-releasing intrauterine devices on endometrial glands, causing atrophy of endometrial glands and, on occasion, the whole functional layer. 5 Fat atrophy at the site of a subdermal contraceptive implant may be specific to the constituents of that particular device.…”
Section: Discussionmentioning
confidence: 99%